2016
DOI: 10.1002/ange.201605865
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von meta‐Terphenyl‐2,2′′‐diolen durch anodische C‐C‐Kreuzkupplungen

Abstract: Die anodische C‐C‐Kreuzkupplung ist eine vielseitig einsetzbare Transformation, die eine gezielte Synthese von Biphenolen und arylierten Phenolen ermöglicht. Wir berichten über einen ebenfalls elektrosynthetischen, metallfreien Ansatz, der einen Zugang zu symmetrischen und nichtsymmetrischen meta‐Terphenyl‐2,2′′‐diolen in guten Ausbeuten und hoher Selektivität ermöglicht. Symmetrische Derivate können durch eine direkte Synthese in einer ungeteilten Zelle gewonnen werden, wohingegen nichtsymmetrische meta‐Terph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The selectivity of the cross‐coupling originates with the interaction of the coupling component with the solvent 1,1,1,3,3,3‐hexafluoroisopropanol (HFIP), which allows the decoupling of nucleophilicity from the oxidation potential to some extent . So far, the synthesis of symmetric and non‐symmetric biphenols, phenol‐arenes, meta ‐terphenyl‐2,2′′‐diols, 2,2′‐diamino‐biaryls, and phenol‐thiophenes was accomplished . With regard to these results and those of many other groups, the electro‐organic synthesis is currently experiencing a renaissance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of the cross‐coupling originates with the interaction of the coupling component with the solvent 1,1,1,3,3,3‐hexafluoroisopropanol (HFIP), which allows the decoupling of nucleophilicity from the oxidation potential to some extent . So far, the synthesis of symmetric and non‐symmetric biphenols, phenol‐arenes, meta ‐terphenyl‐2,2′′‐diols, 2,2′‐diamino‐biaryls, and phenol‐thiophenes was accomplished . With regard to these results and those of many other groups, the electro‐organic synthesis is currently experiencing a renaissance.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that for (2‐hydroxyphenyl)benzofurans the initial phenolic component is incorporated into the final benzofuran product indicates that the mechanistic concourse is more complex compared to recently published arylation reactions . Moreover, when using for example 3‐methylbenzofuran ( 1 c ), the initial methyl group can be found in position 2 of the final benzofuran moiety upon the electroconversion ( 3 c , 3 f , 3 h , and 3 j ).…”
Section: Methodsmentioning
confidence: 99%
“…Anodic coupling reactions are an important and sustainable alternative to conventional methods, as numerous publications have already shown . The coupling reactions of phenols are particularly noteworthy.…”
Section: Methodsmentioning
confidence: 99%
“…The coupling reactions of phenols are particularly noteworthy. Various successfully homo‐ and cross‐coupling reactions of phenols have been carried out so far like the synthesis of symmetric and nonsymmetric biphenols, phenol‐arenes, meta ‐terphenyl‐2,2′′‐diols, 2‐hydroxy‐ para ‐terphenyls, phenol‐thiophenes, phenol‐benzofurans, phenol‐naphthylamines, and phenol‐benzo[ b ]thiophenes . In all of such electrochemical coupling reactions, one particular challenge is to avoid byproducts resulting from homocoupling and over‐oxidation reactions to poly‐ and oligomeric products .…”
Section: Methodsmentioning
confidence: 99%
“…Lips et al reported a highly efficient electrochemical C–C coupling reaction under metal‐free conditions for the synthesis of meta ‐terphenyl‐2,2''‐diols (Scheme 107). [ 85 ] Symmetric terphenyls were obtained via one pot electrolysis, however, non‐symmetric ones required two electrochemical steps.…”
Section: Electrochemical Oxidized Cross‐dehydrogenative Couplingmentioning
confidence: 99%